2010
DOI: 10.1111/j.1471-0528.2010.02763.x
|View full text |Cite
|
Sign up to set email alerts
|

Metformin should be considered in the treatment of gestational diabetes: a prospective randomised study

Abstract: Objective To examine if oral metformin is as effective as insulin in the prevention of fetal macrosomy in pregnancies complicated with gestational diabetes mellitus (GDM).Design Open-label prospective randomised controlled study.Setting Maternity outpatient clinics in a secondary and tertiary level hospital in Finland.Sample One hundred women with GDM who did not attain euglycaemia with diet.Methods Women were randomised to therapy with insulin (n = 50) or oral metformin (n = 50).Main outcome measures Incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
174
5
7

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(200 citation statements)
references
References 21 publications
(58 reference statements)
14
174
5
7
Order By: Relevance
“…In this study, the patients needing additional insulin did not differ significantly with respect to age, parity, their OGTT, or HBA1c values. Study showed no association between BMI, glucose values in OGTT, and a need for additional insulin contrary to the findings of Ijas et al (32) The reason for this different result maybe chance, but the number of subjects in the study by Ijas et al (32) was greater than that in the present study.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…In this study, the patients needing additional insulin did not differ significantly with respect to age, parity, their OGTT, or HBA1c values. Study showed no association between BMI, glucose values in OGTT, and a need for additional insulin contrary to the findings of Ijas et al (32) The reason for this different result maybe chance, but the number of subjects in the study by Ijas et al (32) was greater than that in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…In present study, there was no significant difference in occurrences of neonatal hypoglycaemia and preterm births between metformin and insulin groups. In fact, there were more preterm births in the insulin group than in the metformin group in the study of Mesdaghinia et al (36) There was no difference in incidence of preterm births between the groups in other studies (32,34,35) nor in this study. The risk of Respiratory Distress Syndrome (RDS) was low in this study and was not increased by the use of metformin according to previous studies.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…После исследования MIG было опубликовано мно-жество РКИ, посвященных сравнению метформина с инсулином, которые в большинстве своем подтвердили данные MIG [16][17][18][19][20][21][22][23]. Единственным ключевым отли-чием стало отсутствие тенденции к преждевременному родоразрешению в группе пациенток на метформине, которое было показано в MIG.…”
Section: репродуктивное здоровьеunclassified